ANALISIS WASTE PADA PRODUKSI ES KRIM DENGAN METODE LEAN SIX SIGMA - Nowescophor, Ryu; Salomon, Lithrone Laricha; Doaly, Carla Olivia (Jurnal Mitra Teknik Industri, 2024)
Today, the words "quality" and "productivity" are the main components in supporting the level of success of a company. In addition, companies are also required to produce products quickly, but the products produced must have good quality. This good product quality will greatly affect the profits that will be received by the company. PT XYZ is a company engaged in the production of ice cream. This research was conducted using the lean six sigma method using the DMAIC stage principle. Based on the results of field studies, in the ice cream production process can be found product rejection by 2.5 to 3.5 percent which makes the level of production carried out by the company relatively high. In addition, there is also waste such as defects, overproduction, and inventory that occurs in the production department. Based on the calculation results at the measure stage, it is known that the company's current efficiency level is 33.53%, the DPMO value is 9906 products, and the company's sigma value is 3.83. The analysis stage is carried out by analyzing the causes of defects and waste that occur in the company using the help of tools such as why-why analysis and failure mode and effect analysis. After knowing the root cause of the problem of defects and waste, this study continued by providing various improvement proposals to eliminate existing defects and waste. The research is then continued in the last stage, namely controling, where at this stage further supervision and monitoring of proposed improvements that have been applied to the company. In addition, at this control stage, a recalculation of process capabilities will also be carried out to find out how the impact of improvements that have been made on the company.